Cognitive Function in Patients With Alcoholic and Nonalcoholic Chronic Liver Disease - Brodersen, Carlos (2014)
The aim of the present study was to characterize the neurophysiological profile of cognitive impairment associated with patients with chronic alcoholic and nonalcoholic liver disease. The authors evaluated 43 patients with cirrhotic liver disease: 19 patients with chronic alcohol ingestion and 24 nonalcoholic patients who had been infected with hepatitis B or C virus. Eleven healthy subjects were included as control subjects. A battery of 12 psychological tests was used to investigate cognitive deficits in the patients with chronic liver disease. It was observed that alcoholic patients with chronic liver disease showed a more important cognitive deterioration than those affected by hepatitis B or C virus.